A velhice como intervenção nos modos de vida - Reis, Cleilson Teobaldo dos (2010)
This research was proposed to talk with ways of life engendered by the elderly residents of Vitoria/ES, attending to hear their narratives and what they announce as power and as becoming, causing detours and folds in the production of reality. Specifically, the elderly who refuse to undergo interventions of social assistance policies and that, because of it, evokes the need for analysis on ways to make government policies and practices of research, as well as the ways in which collectively produce life. We use the cartographic perspective as a guiding principle of this research and we take as the main material for our analysis reports produced by a technical team active in the policy of social assistance in the city of Vitoria/ES and also the effects of the narratives from the elderly produced in this research and this researcher, since the elderly chosen refused to have their stories publicized in this work. Referencing in concepts such as becoming minority, biopower, ethics, among others, we reiterate the need to put in question the social assistance policies, as well as the policies of research, that we produce, problematizing the rigidities which they are committed. We say how we are called to open ourselves to the production, the listening and the experience of difference as something that points to other possibles and removes the production of reality of the aggregation and of the predefined and definitive shapes.